Training for Cost-Effectiveness vs. Training as Tax Evasion Tool – A Study on Selected Private Companies in Bangladesh - Hossain, Tanjela; Noor, Md. Asad (Global Disclosure of Economics and Business, 2018)
Bangladeshi organizations consider employee training as an indispensable strategic tool for enhancing employee’s performance. Although training seems to be an expense, it is regarded as an investment. Every company is increasing the amount of the budget on training programs showing the reason that training brings the competitive edge. The study is focused on analyzing the tendency of increasing the training budget to know whether it is an investment or an evasion medium of tax in Bangladesh. A survey has been administered to find the degree of effectiveness of training programs, the utilization of budget on training, the cost-effectiveness of training programs and the possibility of training programs used as a tax evasion medium in Bangladesh. We have collected data through a semi-structured questionnaire from a sample of 200 employees working in 20 private organizations located in Dhaka city. We have observed from our survey that most of the time training programs held in different organizations in Bangladesh are not always effective. Trainees are not getting the most out of it. Contrary to the expectation, the analysis showed that the training budget is not sufficient. Although companies are increasing the amount of the training budget every year, it is not enough to give best results. And the budget is not utilized effectively in many cases. For this, many company’s performance in cost-effectiveness of training is not satisfactory. The formal evaluation method is not followed in every company, and the training programs are not improved always. Every organization doesn’t conduct cost and benefit analysis of training programs. The study has also found that training can be used as a tax evasion tool and in many organizations, it is somewhat being used. Training program opens up the opportunity to include false expenses which increases the total cost. The result of increased expense is a decrease in taxable profit. We have used mean, standard deviation, variance, percentage analysis, hypothesis testing, etc. for statistical analysis.